Pengaruh Profesionalisme, Integritas, Locus of Control dan Kinerja Auditor pada Kualitas Audit - Agustina Trisna Dewi, Luh Ayu; Muliartha RM, Ketut (E-Jurnal Akuntansi, 2018)
This study took the sample of all auditors at the Public Accounting Firm of Bali Province registered in IAPI amounted to 9 KAP, by making 71 auditors, as samples by sampling method jenuh.Pengumpulan data by distributing questionnaires with respondents who returned amounted to 44 people. Analytical techniques in this study using multiple linear regression analysis with SPSS program. Based on the results of the analysis show that professionalism positively affect the quality of audit, integrity has a positive effect on audit quality, locus of control has a positive effect on audit quality and auditor performance has a positive effect on audit quality.It shows that the higher the professionalism, integrity, locus of control and performance auditor then the quality of the resulting audit the better. The results of this study can be considered for the client in choosing an independent auditor to reduce and resolve the conflict of interest between the principal and agent.Selain it for auditors to maintain professionalism, integrity, locus of control and improve performance to be able to produce and improve audit quality. Keywords: professionalism, integrity, locus of control, auditor performance, audit quality.